2011
DOI: 10.4236/health.2011.34039
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease in adults with human immunodeficiency virus infection: a systematic review

Abstract: Objective: To determine the prevalence of chro- nic obstructive pulmonary disease (COPD) in adults with Human Immunodeficiency virus infection (HIV). Design: Systematic review of Medline, Embase, CINAHL, PsycINFO and references from identified papers. Study selection: Studies determining the prevalence of COPD in adults with HIV infection. Independent duplicate data extraction. Study quality was assessed in terms of whether consecutive patients were en- rolled, recruitment and follow-up periods were defined, &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…With HAART therapy, the incidence of opportunistic infections and mortality has been markedly reduced 42 , but the treated HIV + individuals have an increase of chronic aging-related disorders including COPD 2 , 5 , 7 , 43 47 . Several studies have shown the pulmonary/airway abnormalities observed in PLWH, including nonsmokers receiving HAART treatment 9 11 , 13 17 .…”
Section: Discussionmentioning
confidence: 99%
“…With HAART therapy, the incidence of opportunistic infections and mortality has been markedly reduced 42 , but the treated HIV + individuals have an increase of chronic aging-related disorders including COPD 2 , 5 , 7 , 43 47 . Several studies have shown the pulmonary/airway abnormalities observed in PLWH, including nonsmokers receiving HAART treatment 9 11 , 13 17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, chronic HIV-1 infection is associated with several comorbid disorders, including a high incidence of chronic obstructive pulmonary disease manifesting as emphysema (Bhatia and Chow, 2016; Bhatia et al, 2012; Crothers et al, 2006; Crothers et al, 2011; Diaz et al, 1992; Diaz et al, 2000; Diaz et al, 2003; Giantsou, 2011; Kalim et al, 2008; Morris et al, 2011a; Morris et al, 2011b; Naicker et al, 2015; Palella and Phair, 2011; Petrache et al, 2008). The pathogenesis of HIV-associated emphysema is not well understood, with some evidence implicating lung destruction mediated by alveolar macrophages, CD8 T cells, HIV envelope proteins and possibly anti-retroviral drugs (Buhl et al, 1993; George et al, 2009; Green et al, 2014; Kanmogne et al, 2005; Park et al, 2001; Plata et al, 1987; Twigg et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 associated emphysema was originally linked to opportunistic lung infections and intravenous drug use (Beck et al, 2001; Morris et al, 2000). A number of studies, however, have clearly demonstrated that HIV-1 + individuals who have no prior history of pulmonary infection have a higher incidence of emphysema than that of the general population and develop emphysema at an early age, i.e., infection with HIV-1 is a cofactor in the development of COPD (Crothers et al, 2006; Crothers et al, 2011; Diaz et al, 1992; Diaz et al, 2000; Diaz et al, 2003; Giantsou, 2011; Morris et al, 2011a; Morris et al, 2011b; Petrache et al, 2008). The pathogenesis of HIV-associated emphysema is not understood, with some evidence pointing to alveolar macrophage (AM) and CD8 T cell mediators (Buhl et al, 1993; Plata et al, 1987; Twigg et al, 1999), direct effects on the lung of HIV proteins such as Env and Tat (Green et al, 2014; Kanmogne et al, 2005; Park et al, 2001) and adverse effects of anti-retroviral therapies (George et al, 2009).…”
Section: Introductionmentioning
confidence: 99%